EVALUATION OF SEROLOGICAL TESTS FOR DIAGNOSIS OF BRUCELLOSIS IN CAMELS FOR EXPORT AND CONTROL PURPOSES IN THE SUDAN (Journal of Veterinary Medicine and Animal Production, 2022)
Prevalence of brucellosis in camels in the Sudan is high and the disease affects their productivity and is a main constraint to their export to the Arabian Peninsula. This study was designed to compare the Rose Bengal Plate Test (RBPT), the modified m(RBPT) and competitive ELISA (c ELISA) for examination of 492 camel serum samples from Kassala State for brucellosis for export and control purposes. Of the total, 383(77.8%) samples were examined with the three tests, and 109(22.2%) with the RBPT and mRBPT and 463 samples were examined with the Serum Agglutination Test (SAT) , each with both Brucella abortus ( B. abortus) and Yersinia enterocolitica 0:9 ( Y. enterocolitica 0:9) SAT antigens. After incubation at 37ºC for 24 hours and reading the SATs , the supernatants of each were tested for agglutination with the heterologus antigen for detection of Y. enterocolitica O:9 antibodies. The results of RBPT, mRBPT and cELISA agreed in 28.5% of the positive, 30.3% of the negative and disagreed in 3.9% of false negative and 36.3% of false positive samples; and 1% of the samples were negative with the RBPT, positive with the mRBPT and cELISA. Of the samples examined with the RBPTs, the results agreed in 15.6% of the negative, 66.1% of the positive and disagreed in 18.4% of the negative with the RBPT and positive with the mRBPT. Of the 463 samples, 2.6% were suspected to contain Y. enterocolitica 0:9 antibodies. It is recommended to screen camels for brucellosis for export and control purposes with the mRBPT, confirm the positive cases with a confirmatory test for control and reexamine the negative cases after two months with the test for to make sure that there are no false negative camels.